Pengaruh Kecepatan Pengadukan Proses Rheocasting terhadap Struktur Mikro dan Fluiditas Paduan Al-Cu - Putra, Muhammad Rezki Fitri; Suprapto, Wahyono; Sonief, Achmad As’ad (Jurnal Rekayasa Mesin, 2019)
Rheocasting with the aim of developing and offering solutions to problems related to the casting process. Rheocasting is a casting process that utilizes solidification agitation to change the dendritic structure to non-dendrite (globular) by giving a variation of the stirring speed. Al-Cu is a metal material that has high strength-to-weight ratio characteristics from steel, good fatigue resistance, and heat-treatable. But fluidity is low, this triggers casting defects such as shrinkage and miss-run. The defect occurs because the cooling process of liquid metal is not uniform or there is gas trapped in molten metal. Defects in casting can significantly reduce material mechanical properties. The results show morphological changes in the dendrites to rosette to globular with increased stirring speed and grain diameter decreasing with increasing stirring speed. Increasing the stirring speed also produces a positive trend of the fluidity value of Al-Cu alloys in each mold thickness.